2016
DOI: 10.1128/jvi.03122-15
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Influenza D Virus in Cattle

Abstract: Cattle have been proposed as the natural reservoir of a novel member of the virus family Orthomyxoviridae, which has been tentatively classified as influenza D virus (IDV). Although isolated from sick animals, it is unclear whether IDV causes any clinical disease in cattle. To address this aspect of Koch's postulates, three dairy calves (treatment animals) held in individual pens were inoculated intranasally with IDV strain D/bovine/Mississippi/C00046N/2014. At 1 day postinoculation, a seronegative calf (conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
187
4
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(228 citation statements)
references
References 17 publications
(37 reference statements)
8
187
4
7
Order By: Relevance
“…At that point, viruses, if any, might have already been cleared, leaving only the pulmonary lesions. Secondly, some viruses, such as IDV (Ferguson et al, ), preferentially infect the upper respiratory tract, not the lung. In the current study, IDV was detected in the lung of only 1/130 cattle, compared with 16/116 upper respiratory tract samples in our previous study (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…At that point, viruses, if any, might have already been cleared, leaving only the pulmonary lesions. Secondly, some viruses, such as IDV (Ferguson et al, ), preferentially infect the upper respiratory tract, not the lung. In the current study, IDV was detected in the lung of only 1/130 cattle, compared with 16/116 upper respiratory tract samples in our previous study (Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that 0.6% and 2.4% of healthy cattle were infected by this virus (Ferguson et al., ; Jiang et al., ). An experimental infection with this virus showed that several infected cattle were asymptomatic (Ferguson et al., ). In this study, follow‐up evaluations of the health statuses of the cattle after sampling were not conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies demonstrated cattle, swine, ferrets, and guinea pigs are susceptible to IDV infection (Collin et al, 2015; Ferguson et al, 2016; Hause et al, 2014; Hause et al, 2013; Sreenivasan et al, 2015). Serologic assays in two independent studies showed that IDV could potentially infect humans, although seropositivity rates in the studies differed.…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies reported 91% seropositivity among 35 persons working with cattle (White et al, 2016), and the other reported only 1% seropositivity among 741 persons with suspected high exposure to IDV (Eckard, 2016). Nevertheless, epidemiologic, serologic, and pathologic studies have suggested cattle are the primary natural reservoir for IDV (Collin et al, 2015; Ducatez et al, 2015; Ferguson et al, 2015; Ferguson et al, 2016; Hause et al, 2014; Jiang et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation